FRI0539 Impact of the implementation of a fracture liaison service in pharmaceutical expenses for osteoporosis. (15th June 2017) - Naranjo, A; Ojeda, S; Rodriguez, S; Bernardos, I; Molina, A; Nuez, F de la; Negrin, M
Abstract : Background: In 2012 a Fracture Liaison Service (FLS) was implemented in Hospital Dr Negrin Objectives: To analyze the economic impact of the FLS on pharmaceutical expenditure for osteoporosis. Methods: Expenditure on osteoporosis medication (government inpunt) was collected from January 1th, 2011 to October 1th, 2016. The data distinguish group I (calcium and vitamin D), group II (Bisphosphonates, denosumab, SERM, strontium and teriparatide) and total expenditure (sum of groups I and II). Intravenous bisphosphonates were not included. Gran Canaria island is organized in two health areas; the North and the South areas. The population aged >65 years in the North and South areas in 2016 were 63.535 and 52.453 people, respectively. In the Gran Canaria South area there is no formal FLS. An estimate of the number of cases of fracture attended in FLS and that was still under treatment in septiembre 2016 was calculated. Results: The total expenditure on prescriptions for osteoporosis in 2016 (January to September) in the North area was 1, 226, 702 €, while in the South area it was 1, 069, 606 € (a 14% higher in the North area). The expenditure in 2016 for group II (bisphosphonates and equivalents) was 799, 840 € and 656, 301 € respectively (22% higher in the North area). The evolution of the percentage of total expenditure in osteoporosis for the North area in relation to the total of Gran Canaria was the following: 53.6% in 2011; 54.2% in 2012; 54.4% in 2013; 54.3% in 2014; 53.4% in 2014 and 53.4% in 2016 (Figure). For group II drugs, the percentage of 55% for the North area did not change between 2011 and 2016. The number of drug prescriptions for group I was 7, 551 units in the North area and 7, 732 in the South area. For group II, the figures were 3, 917 units in the North area and 2, 873 units in the South area. That is, the prescription of group I drugs in the January-September 2016 period was similar in both areas (2% higher in the South area), while for Group II it was 36% higher in the North area, being this difference stable between 2011 and 2016. Between 2012 and 2016, 1, 297 patients have been evaluated in the FLS, of which 75% have indication of bisphosphonate or equivalents. The average adherence to treatment at 12 and 24 months is 70% (1). The estimate is that approximately 681 patients (17%) of the 3, 917 who receive a drug from group II in the North area in October 2016 derivates from the FLS. Conclusions: The implantation of a FLS, despite supposing around 16% of the percentage of patients treated with bisphosphonates and equivalents in the health area Gran Canaria North derivates from the FLS has not led to an increase in pharmaceutical expenditure for osteoporosis. We believe that one of the reasons for the non-increase in spending is the rational use of drugs for osteoporosis. References: Naranjo A et al. Osteoporos Int. 2015;11:2579. Disclosure of Interest: None declared